2021
DOI: 10.3389/fpls.2021.640512
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Produce Grapefruit-Like Citrus Varieties With a Low Furanocoumarin Content and Distinctive Flavonoid Profiles

Abstract: Pummelos and hybrids, such as grapefruits, have high furanocoumarin and low flavonoid contents. Furanocoumarins interact negatively with certain drugs, while flavonoids are antioxidant compounds with health benefits. To obtain new grapefruit-like varieties with low furanocoumarin and high flavonoid contents, diploid and triploid hybrid populations from crosses between diploid and tetraploid “Clemenules” clementine and diploid “Pink” pummelo were recovered and analyzed. With regard to furanocoumarins, triploids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In addition, the anti‐inflammatory activities of EOs are often related to their analgesic properties (de Cassia da Silveira e Sa et al., 2013), which further support their use in health care, but also the potential clinical significance of our findings. Further, given that the consumption of grapefruit has decreased due to the interference of some compounds with drug absorption, there is a high need for obtaining grapefruit‐like citrus varieties without such unfavorable effects (Garcia‐Lor et al., 2021). Moreover, playing an important role in the onset and constancy of the inflammatory process, some pro‐inflammatory cytokines, such as IL‐6 and TNF‐α (Kany et al., 2019), are important targets for developing new anti‐inflammatory agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the anti‐inflammatory activities of EOs are often related to their analgesic properties (de Cassia da Silveira e Sa et al., 2013), which further support their use in health care, but also the potential clinical significance of our findings. Further, given that the consumption of grapefruit has decreased due to the interference of some compounds with drug absorption, there is a high need for obtaining grapefruit‐like citrus varieties without such unfavorable effects (Garcia‐Lor et al., 2021). Moreover, playing an important role in the onset and constancy of the inflammatory process, some pro‐inflammatory cytokines, such as IL‐6 and TNF‐α (Kany et al., 2019), are important targets for developing new anti‐inflammatory agents.…”
Section: Discussionmentioning
confidence: 99%
“…It should be mentioned that the chemical composition of Citrus oils is different and depends on origin, season, ripening stage, climate, method of extraction, genetic background, age, and so on (Dosoky & Setzer, 2018; Khalil et al., 2022). In addition, it has been shown that environmental conditions and maturation may influence the amount of the compounds that interfere with drugs, and also there are differences in its mount between harvest times and seasons, which, further, all together make evaluation and selection of new varieties more difficult in practice (Garcia‐Lor et al., 2021). The novelty of the present study is that GEOs were obtained from grapefruit peel using a particular type of stationary phase and Fr‐GEO with high content in aldehydes, thus influencing the product quality and its biological effects and making the combination of volatile compound unique compared to what has been already reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Citrus paradisi belongs to the Rutaceae family, commonly known as grapefruit is considered a functional food; its nutrient content represents is a valuable source of vitamin C, carbohydrates, dietary fiber, various B vitamins, minerals, as well as pharmacologically active compounds, such as carotenoids, and free (aglycon) and glycosylated flavonoids [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we employed two citrus species at the diploid and tetraploid levels that are very interesting parents for breeding programs ( Starrantino and Recupero, 1981 ; Navarro et al, 2015 ) and display different pollen performances, “Clemenules” clementine and blood orange [ C. sinensis (L.) Osbeck]. “Clemenules” clementine, a natural hybrid between mandarin and sweet orange ( Deng et al, 1996 ), is one of the most important and widely cultivated mandarin varieties in the Mediterranean Basin, especially in Spain, because of its excellent organoleptical properties, sexual characteristics, lack of furanocoumarins (FCs), and notable amount of flavonoids ( Garcia-Lor et al, 2021 ). It presents good fertility at the diploid level but is not fertile at the tetraploid level.…”
Section: Introductionmentioning
confidence: 99%